2013
DOI: 10.2337/dc12-2390
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of the Treatment of Youth-Onset Type 2 Diabetes

Abstract: OBJECTIVEData related to the safety and tolerability of treatments for pediatric type 2 diabetes are limited. The TODAY clinical trial assessed severe adverse events (SAEs) and targeted nonsevere adverse events (AEs) before and after treatment failure, which was the primary outcome (PO).RESEARCH DESIGN AND METHODSObese 10- to 17-year-olds (N = 699) with type 2 diabetes for <2 years and hemoglobin A1c (A1C) ≤8% on metformin monotherapy were randomized to one of three treatments: metformin, metformin plus rosigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, accumulating evidence provides support for more appropriate goals. The TODAY study showed that hypoglycemia is rare in adolescents with type 2 diabetes, even with insulin therapy ( 73 ), suggesting that more stringent A1C targets are acceptable. Also in TODAY, individuals with an A1C of >6.3% after 3 months of metformin or an increasing A1C, even in the nondiabetes range ( 74 ), had a substantially increased risk for loss of glycemic control, likely reflecting a greater degree of β-cell dysfunction ( 75 , 76 ).…”
Section: Glycemic Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, accumulating evidence provides support for more appropriate goals. The TODAY study showed that hypoglycemia is rare in adolescents with type 2 diabetes, even with insulin therapy ( 73 ), suggesting that more stringent A1C targets are acceptable. Also in TODAY, individuals with an A1C of >6.3% after 3 months of metformin or an increasing A1C, even in the nondiabetes range ( 74 ), had a substantially increased risk for loss of glycemic control, likely reflecting a greater degree of β-cell dysfunction ( 75 , 76 ).…”
Section: Glycemic Targetsmentioning
confidence: 99%
“…This can be done alone or in combination with metformin, unless metformin is contraindicated. Because studies indicate that adherence with insulin therapy is a challenge in youth with type 2 diabetes ( 73 , 119 ), starting with a single daily dose of a long-acting insulin analog (glargine [Lantus, Basalglar, Toujeo], detemir [Levemir], or degludec [Tresiba]) may be preferred. Premixed insulins may be appropriate in some circumstances.…”
Section: Pharmacologic Approaches To Glycemic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse effects related to insulin use include weight gain and hypoglycemia. Hypoglycemia is rare in youth with T2DM due to insulin resistance [ 18 ]. Insulin regimens should be carefully tailored to lifestyle and individual needs.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…However, more stringent goals such as less than 6.5% may be appropriate for selected individuals if the goal can be met without significant hypoglycemia or other adverse effects and in those with short duration of diabetes or patients who receive therapy with lifestyle or metformin only with significant weight improvement [ 15 ]. The lower target of <6.5% in selected instances is supported by the evidence that hypoglycemia in patients with T2DM receiving insulin is rare [ 18 ] and A1C > 6.3% after 3 months of metformin or any increasing A1C even in the non-diabetes range was associated with increased risk for loss of glycemic control in the TODAY study [ 10 ]. The A1C targets should also be individualized based on baseline A1C at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%